Muatan kecerdasan ekologis dalam bahan ajar BIPA seri umum “Sahabatku Indonesia” - Hubbi Saufan Hilmi; Sri Wahyuni; Asriani Thahir; Fitria Wulan Sari (Jurnal Bahasa Indonesia bagi Penutur Asing, 2023)
This study aims to describe and explain the content of ecological intelligence contained in BIPA teaching materials, namely BIPA books 1-7 “Sahabatku Indonesia”. This research is a qualitative descriptive research using content analysis method. The data in this study are in the form of text contained in the BIPA 1-7 book “Sahabatku Indonesia” which contains the content of ecological intelligence. The results indicate that the content of ecological intelligence in BIPA teaching materials identifying components of ecosystems, understanding the functions and uses of ecosystem components, understanding natural and environmental management systems, understanding environmental values, showing concern for environmental damage or environmental pollution, solving problems arising from environmental impacts, managing/conserving natural resources, and making positive use of the environment. The book that constains the most content of ecological intelegence is the BIPA 5 book “Sahabatku Indonesia” with 10 materials containing ecological intelligence.